Pengaruh promosi dan harga terhadap keputusan pembelian franchise M3 Fried Chicken di Kabupaten Tangerang - Muhamad Miraz Fauzi; Jaka Slameta; Leni Hartati (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2023)
This research aims to determine the influence of promotion and price on purchasing decisions for the M3 Fried Chicken franchise in Tangerang Regency. The method used is Quantitative Research. The sampling method is non propbability. The number of samples in this study was 58 respondents. Data collection techniques use questionnaires, observation and literature study. Then the test tool used was SPSS (Statistical Package for The Social Science) software version 20 with a population and sample of 58 respondents. The research results show that there is a partial T influence of promos and prices on purchasing decisions. Promotion with a value of 3,835 then a price of 2,353 is greater than the T table of 2.004 and is significantly smaller than 0.05. So it can be concluded that the promotion and price variables influence the purchasing decision variable. The results of this research are simultaneous with a calculated F value of 63,610 which is greater than F table 3.16, so the promotion and price variables have a joint influence on the purchasing decision variable. It can be concluded based on the research results that promotion and price on purchasing decisions have a positive and significant relationship.